Analisis Pengungkapan Corporate Social Responsibility PT. Aneka Tambang Tbk Berdasarkan Global Reporting Initiatives (GRI) Dan Kaitannya Terhadap PROPER - Nurul Addini; Charoline Cheisviyanny; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to analyze: 1) The level of Corporate Social Responsibility (CSR) disclosure of PT Aneka Tambang, Tbk for the year 2017 and 2018 based on the GRI G4 Guideliness, 2) The similarity of each indicator contained in GRI G4 with PROPER which are issued by the Indonesian Ministry of Environment. This is a descriptive qualitative research using Sustainability Report of PT Aneka Tambang, Tbk for the year 2017-2018. Data for this study were secondary data were analysed using content analysis technique. The results show that: 1) Based on the result of content analysis on the level of disclousure of economic, social and environmental performance indicators on Corporate Social Responsibility disclousure of PT ANTAM is higher for 2017 compared to those of 2018. The breadth and depth ofCorporate Social Responsibility disclosure of PT ANTAM in 2017, is better compared to those of 2018. 2) In GRI G.4 especially enviromental aspects, there are several indicator items that have similarities with PROPER valuation indicator